COMPARISON OF DIFFERENT CRITERIA IN THE PREVALENCE OF METABOLIC SYNDROME IN STUDENTS FROM PARANAVAÍ, PARANÁ - Flávio Ricardo Guilherme; Matheus Amarante do Nascimento; Carlos Alexandre Molena-Fernandes; Vânia Renata Guilherme; Stevan Ricardo dos Santos; Rui Gonçalves Marques Elias; Wilson Rinaldi
ABSTRACT Objective: To investigate the difference in the proportion of students with metabolic syndrome, diagnosed according to different criteria. Methods: The sample consisted of 241 students (136 boys and 105 girls) aged 10 to 14 years, from public and private schools in Paranavaí, Paraná. We used three distinct diagnostic criteria for metabolic syndrome, considering the presence of at least three of the following risk factors: increased waist circumference, hypertension, fasting hyperglycemia, low HDL-C, and elevated triglycerides. Results: The prevalence of metabolic syndrome found was 1.7% (confidence interval of 95% - 95%CI 0-3.3) for the IDF criterion; 3.3% (95%CI 1.0-5.6) for Cook; and 17.4% (95%CI 12.6-22.3) for Ferranti. Analyzing the criteria in pairs, the agreement between IDF and Cook was 97.5% (k=0.95); between IDF and Ferranti, 83.4% (k=0.67); and between Cook and Ferranti, 85.9% (k=0.72). Onlyone student (0.4%) was diagnosed with metabolic syndrome solely by the IDF criterion, while 34 (14.1%) were diagnosed exclusively by Ferranti. The comparison of the three criteria showed that Ferranti presented the highest proportion of metabolic syndrome (p<0.001), and Cook had a greater proportion than IDF (p<0.001). Conclusions: We found a significant difference in the proportion of metabolic syndrome in the three criteria. The choice of which criterion to use can compromise not only the percentage of metabolic syndrome prevalence but also interfere in strategies of intervention and prevention in children and adolescents with and without metabolic syndrome, respectively.